Spectrophotometric Micro Determination of Promrthazinc Hydrochloride in Pharmaceutical Preparations Via Oxidative Coupling Reaction with Sulphanilamide and in the Presence of Ferric Chloride (Baghdad Science Journal, 2005)
A simple, accurate and sensitive spectrophotometric method for the determination of promethazine hydrochloride is described.